2014
DOI: 10.1016/j.freeradbiomed.2013.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Developmental susceptibility of neurons to transient tetrahydrobiopterin insufficiency and antenatal hypoxia–ischemia in fetal rabbits

Abstract: Tetrahydrobiopterin (BH 4 ) is important for normal brain development as congenital BH 4 deficiencies manifest movement disorders at different childhood ages. BH 4 transitions from very low levels in fetal brains to higher 'adult' levels postnatally, with the highest levels in the thalamus. Maternal supplementation with BH 4 -precursor, sepiapterin, reduces postnatal motor deficits and perinatal deaths following 40-min fetal hypoxia-ischemia (HI) at 70% gestation, suggesting brain BH 4 is important in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…However, we were unable to support the survival of the neural cells in culture beyond 7 days. Our research is aligned with other studies showing that it is difficult to extend the culture period of fetal neurons in vitro [143132]. Despite the incorporation of novel reagents, such as RA in combination with other prosurvival factors such as bFGF, we still could not support survival long-term in the dish.…”
Section: Discussionsupporting
confidence: 67%
“…However, we were unable to support the survival of the neural cells in culture beyond 7 days. Our research is aligned with other studies showing that it is difficult to extend the culture period of fetal neurons in vitro [143132]. Despite the incorporation of novel reagents, such as RA in combination with other prosurvival factors such as bFGF, we still could not support survival long-term in the dish.…”
Section: Discussionsupporting
confidence: 67%
“…The present study also explains the discrepancy of ex vivo survival of neuronal cells isolated from different brain regions being unrelated to the differences in endogenous levels in our previous publication [9]. Based on tetrahydrobiopterin levels, the E22 thalamus neurons at 70% gestation were expected to show increased resistance to H–I injury compared to cortical neurons with a comparatively lower tetrahydrobiopterin content.…”
Section: Discussionsupporting
confidence: 61%
“…Previously we showed that cumulative increases of tetrahydrobiopterin in the thalamus, basal ganglia, and cortex occur in naïve fetal brains between 70%–92% gestation, suggesting a role in normal development [8]. In a study to examine if tetrahydrobiopterin influenced neuronal survival, neuronal cultures from different brain regions of basal ganglia, cortex, and thalamus at 70% and 92% gestation, we showed differential regional susceptibility to ex vivo tetrahydrobiopterin levels, especially following H–I, with the thalamus being most vulnerable in the preterm age [9]. Increasing tetrahydrobiopterin, however, improved neuronal survival after H–I especially in the premature thalamus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different survival rates are found in ex vivo primary neuronal cultures from the basal ganglia, cortex, and thalamus following in vivo HI. Thalamic cells from 70% gestation exhibit the lowest survival rate in a BH 4 -free milieu, in control and HI groups [71] . HI but not control cells are amenable to rescue with supplemented ex vivo BH 4 , suggesting a causal relationship between HI injury and BH 4 -dependent pathways.…”
Section: Tetrahydrobiopterin and Fetal Brain Himentioning
confidence: 92%
“…The fetal rabbit model indicates that BH 4 pathway is a target of HI ( Fig. 4 ), and a two-hit model likely explain susceptibility to injury [71] . The first condition necessary is low developmental, like in prematurity, BH 4 levels.…”
Section: Low Developmental Bh 4 Levels In Brain Himentioning
confidence: 99%